The duel of puberty in the context of Latin American social isolation - Ledesma-Pérez, Fernando; Cruz-Montero, Juana; Holgado-Quispe, Ana; Ruiz-Salazar, Jenny; Holguin-Alvarez, Jhon (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Grief is a hard psychological process to cope with death due to the appearance of Covid-19 in Peru. When infected people died as a result of the infection, they were cremated at the hospital's expense, and relatives were given a small box in which they were told that the ashes of their deceased were. Interviews with 11-year-old children, parents and hospital psychologists; they revealed pictures of anxiety or anguish, due to generalized fear. The social and school protection factors were not very sustainable to cope with the penalty.